2020
DOI: 10.7717/peerj.10256
|View full text |Cite
|
Sign up to set email alerts
|

Genomic characterization and phylogenetic analysis ofSalmonella entericaserovar Javiana

Abstract: Salmonella enterica serovar Javiana is the fourth most reported serovar of laboratory-confirmed human Salmonella infections in the U.S. and in Tennessee (TN). Although Salmonella ser. Javiana is a common cause of human infection, the majority of cases are sporadic in nature rather than outbreak-associated. To better understand Salmonella ser. Javiana microbial population structure in TN, we completed a phylogenetic analysis of 111 Salmonella ser. Javiana clinical isolates from TN collected from Jan. 2017 to Oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 139 publications
(194 reference statements)
0
6
0
Order By: Relevance
“…ceBGs are equivalent to eBurst groups (eBGs) from legacy 7-gene MLST and correspond to serovar designations ( 20 , 21 ). Typically, monophyletic serovars consist of a single eBG, while polyphyletic serovars consist of multiple eBGs ( 22 25 ). Lineage I isolates belonged to ceBGs 370, 12161, and 135213, lineage II isolates belonged to ceBGs 44, 391, and 401, and lineage III isolates belonged to ceBGs 120 and 65092 ( Table 1 , Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…ceBGs are equivalent to eBurst groups (eBGs) from legacy 7-gene MLST and correspond to serovar designations ( 20 , 21 ). Typically, monophyletic serovars consist of a single eBG, while polyphyletic serovars consist of multiple eBGs ( 22 25 ). Lineage I isolates belonged to ceBGs 370, 12161, and 135213, lineage II isolates belonged to ceBGs 44, 391, and 401, and lineage III isolates belonged to ceBGs 120 and 65092 ( Table 1 , Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The original prediction for amikacin resistance was 100%, due to all isolates containing the aac(6′)-Iaa gene. However, this gene has been shown to be cryptic and no longer confer phenotypic resistance to aminoglycosides ( 25 , 47 , 48 ), so the results were adjusted accordingly. The NARMS human clinical ABR data were downloaded from NARMS Now ( 33 ) for comparison purposes.…”
Section: Methodsmentioning
confidence: 99%
“…Using the approach described in Methods - Putative non-monophyletic serovar prediction, we found 265/537 (49.3 %) putative non-monophyletic serovars, including Enteritidis, Typhimurium, Newport, Kentucky and Javiana. Subsequent manual literature curation indicated that 18 % of the evaluated serovars had previously been reported to be polyphyletic or paraphyletic [5, 37–48]. To confirm the validity of our approach to predict monophyly, we performed maximum-likelihood-based phylogenetic reconstruction of two serovars Choleraesuis and Paratyphi C that were predicted as non-monophyletic by our approach, but previously reported as monophyletic [49].…”
Section: Resultsmentioning
confidence: 99%
“…Using the approach described in Methods -Putative non-monophyletic serovar prediction, we found 265/537 (49.3 %) putative non-monophyletic serovars, including Enteritidis, Typhimurium, Newport, Kentucky and Javiana. Subsequent manual literature curation indicated that 18 % of the evaluated serovars had previously been reported to be polyphyletic or paraphyletic [5,[37][38][39][40][41][42][43][44][45][46][47][48].…”
Section: Characterization Of Putative Non-monophyletic Serovarsmentioning
confidence: 99%
“…By this approach, we found 265/537 (49.3%) putative non-monophyletic serovars including Enteritidis, Typhimurium, Newport, Kentucky, and Javiana. Subsequent manual literature curation indicated that 18% of the evaluated serovars had been previously reported to be polyphyletic or paraphyletic (5,(33)(34)(35)(36)(37)(38)(39)(40)(41). Furthermore, the evaluation of the maximum distance required to link genomes of the same in-silico serovar assignments in a single cluster revealed genomes of 209/537 (38.9%) serovars required a distance of >2,000 allelic differences to be linked in a single cluster (Fig.…”
Section: Characterization Of Putative Non-monophyletic Serovarsmentioning
confidence: 95%